1998
DOI: 10.1086/515265
|View full text |Cite
|
Sign up to set email alerts
|

Field Trial of a Vaccine against New World Cutaneous Leishmaniasis in an At‐Risk Child Population: Safety, Immunogenicity, and Efficacy during the First 12 Months of Follow‐Up

Abstract: The safety, immunogenicity, and efficacy of a vaccine against cutaneous leishmaniasis in rural Ecuadorian children was assessed in a randomized, controlled, double-blinded study. Vaccine group subjects received 2 intradermal doses of a whole, killed promastigote vaccine cocktail plus bacille Calmette-Guérin (BCG) adjuvant. Control subjects got 2 doses of BCG only. The subjects who received both vaccination doses, 438 in the vaccine group (79.3%) and 406 in the control group (83.4%), were followed for 12 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 26 publications
3
49
0
2
Order By: Relevance
“…The data obtained from this experiment, combined with the significant increase in the antigen-stimulated spleen cell proliferative response after vaccination demonstrate the immunogenic efficacy of the single strain candidate vaccine. The current results confirm those conducted by other groups working with candidate vaccines formulated with different Leishmania strains that showing the immunogenicity of the candidate vaccine is maintained with both merthiolate and phenolate preservatives (Mayrink et al 1979, Mendonça et al 1995, Armijos et al 1998, 2004.…”
Section: D (405nm)supporting
confidence: 90%
“…The data obtained from this experiment, combined with the significant increase in the antigen-stimulated spleen cell proliferative response after vaccination demonstrate the immunogenic efficacy of the single strain candidate vaccine. The current results confirm those conducted by other groups working with candidate vaccines formulated with different Leishmania strains that showing the immunogenicity of the candidate vaccine is maintained with both merthiolate and phenolate preservatives (Mayrink et al 1979, Mendonça et al 1995, Armijos et al 1998, 2004.…”
Section: D (405nm)supporting
confidence: 90%
“…Extensive vaccination trials in Brazil and Ecuador against cutaneous leishmaniasis in humans have demonstrated that a cocktail of five killed Leishmania stocks or a single strain of L. amazonensis induces protection from natural infection [1,13,23,32]. However, to date, the protection efficacy of these or other vaccines in dogs against visceral leishmaniasis is highly controversial [15,28,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…A vaccination trial with killed cocktail of promastigotes was conducted in the subtropical-Ecuador (Armijos et al 1998) showing significant protection during the first 12 months (72.9%). Protection declined until month 60 of follow-up, with no difference in protection rate between the vaccinated and placebo groups (Armijos et al 2003).…”
Section: Prevention and Control Measuresmentioning
confidence: 99%